Stem girdling evidences a trade-off between cambial activity and sprouting and dramatically reduces plant transpiration due to feedback inhibition of photosynthesis and hormone signaling - López, Rosana; Brossa, Ricard; Gil, Luis; Pita, Pilar (Frontiers in Plant Science, 2015)
The photosynthesis source-sink relationship in young Pinus canariensis seedlings was modified by stem girdling to investigate sprouting and cambial activity, feedback inhibition of photosynthesis, and stem and root hydraulic capacity. Removal of bark tissue showed a trade-off between sprouting and diameter growth. Above the girdle, growth was accelerated but the number of sprouts was almost negligible, whereas below the girdle the response was reversed. Girdling resulted in a sharp decrease in whole plant transpiration and root hydraulic conductance. The reduction of leaf area after girdling was strengthened by the high levels of ABA found in buds which pointed to stronger bud dormancy, preventing a new needle flush. Accumulation of sugars in leaves led to a coordinated reduction in net photosynthesis (AN) and stomatal conductance (gS) in the short term, but later (gS below 0.07 mol m-2 s-1) AN decreased faster. The decrease in maximal efficiency of photosystem II (FV/FM) and the operating quantum efficiency of photosystem II (ΦPSII) in girdled plants could suggest photoprotection of leaves, as shown by the vigorous recovery of AN and ΦPSII after reconnection of the phloem. Stem girdling did not affect xylem embolism but increased stem hydraulic conductance above the girdle. This study shows that stem girdling affects not only the carbon balance, but also the water status of the plant.